Everyday medical ethics and law - Sommerville, Ann (John Wiley & Sons, 2013)
Everyday Medical Ethics and Law is based on the core chapters of Medical Ethics Today, focussing on the practical issues and dilemmas common to all doctors. It includes chapters on the law and professional guidance relating to consent, treating people who lack capacity, treating children and young people, confidentiality and health records. The title is UK-wide, covering the law and guidance in each of the four nations. Each chapter has a uniform structure which makes it ideal for use in learning and teaching. ""10 Things You Need to Know About ... "" introduces the key poi.